The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1371/journal.pone.0004039
|View full text |Cite
|
Sign up to set email alerts
|

BMP-7 Does Not Protect against Bleomycin-Induced Lung or Skin Fibrosis

Abstract: Bone morphogenic protein (BMP)-7 is a member of the BMP family which are structurally and functionally related, and part of the TGFβ super family of growth factors. BMP-7 has been reported to inhibit renal fibrosis and TGFβ1-induced epithelial-mesenchymal transition (EMT), in part through negative interactions with TGFβ1 induced Smad 2/3 activation. We utilized in vivo bleomycin-induced fibrosis models in the skin and lung to determine the potential therapeutic effect of BMP-7. We then determined the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 39 publications
(58 reference statements)
2
39
0
Order By: Relevance
“…In a mouse model of bleomycin-induced fibrosis, systemically administered recombinant BMP7 did not affect fibrosis in either the lung or skin and no effect on expression of pro-fibrotic genes by lung fibroblasts was observed [67]. This suggests that BMP7 may have diverse, even opposing, roles in different tissues.…”
Section: Bmps Emt and Fibrotic Diseasementioning
confidence: 95%
“…In a mouse model of bleomycin-induced fibrosis, systemically administered recombinant BMP7 did not affect fibrosis in either the lung or skin and no effect on expression of pro-fibrotic genes by lung fibroblasts was observed [67]. This suggests that BMP7 may have diverse, even opposing, roles in different tissues.…”
Section: Bmps Emt and Fibrotic Diseasementioning
confidence: 95%
“…BMP-7 is thought of as anti-fibrotic, and has been the focus of many groups who demonstrated its anti-fibrotic activity in models of diabetic nephropathy and other kidney fibrotic diseases [5,[12][13][14][15][16][17]. To date, however, efforts to translate these data into BMP-7-centred treatment of fibrosis have been rather slow to develop [18,19] Canonical BMPs signalling involves the Smad pathway, where BMP dimers bind to type I and type II BMP receptors leading to the formation of a hexameric complex, triggering receptor phosphorylation. This leads to phosphorylation of R-Smads (Smad1/5/8) and complex formation with co-Smad4 which translocates to the nucleus to regulate BMP target gene expression [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that increased collagen turnover and fibrotic changes are earlier events within 14 days in the BLMinduced fibrosis [8][9][10][11] and these changes were used commonly as a pulmonary fibrosis model. Signs of fibrosis were observed at 7 days after BLM administration [8].…”
mentioning
confidence: 99%